2018
DOI: 10.1002/cjas.1492
|View full text |Cite
|
Sign up to set email alerts
|

Which Dimension of Corporate Social Responsibility is a Value Driver in the Oil and Gas Industry?

Abstract: The oil and gas (O&G) industry suffers from a negative perception of poor sustainability. O&G companies are therefore engaged in several socially sustainable activities related to community development and environmental protection. This article determines whether the social, environmental, and economic dimensions of corporate social responsibility (CSR) are equally value-additive to O&G companies. We measure the company-specific level of CSR activities from the information provided in the annual financial repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 70 publications
(118 reference statements)
0
32
1
1
Order By: Relevance
“…Three areas of CSR recurring in most definitions are economic, social, and environmental (Chowdhury et al 2019;Marí-Farinós 2017;Uribe-Macías et al 2018). The economic area of CSR has evolved from the sole obligation of accountability to shareholders (Carroll 1991;Friedman 1962;Friedman 1970) and analyzing the impact of actions on financial performance, to broadening its scope in the sense of considering other aspects, such as the capacity to create jobs, research leading to the discovery of new resources or new applications for them, as well as innovation and the promotion of technological progress (Jamali 2008).…”
Section: The Development Of Csr In the Business Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Three areas of CSR recurring in most definitions are economic, social, and environmental (Chowdhury et al 2019;Marí-Farinós 2017;Uribe-Macías et al 2018). The economic area of CSR has evolved from the sole obligation of accountability to shareholders (Carroll 1991;Friedman 1962;Friedman 1970) and analyzing the impact of actions on financial performance, to broadening its scope in the sense of considering other aspects, such as the capacity to create jobs, research leading to the discovery of new resources or new applications for them, as well as innovation and the promotion of technological progress (Jamali 2008).…”
Section: The Development Of Csr In the Business Worldmentioning
confidence: 99%
“…Many of the research studies carried out on CSR have found relationships between the company's social, environmental, and financial and economic performance (Brogi and Lagasio 2019;Chowdhury et al 2019;Taliento et al 2019), concluding that the three dimensions are interconnected, and joint action ensures long-term sustainability. Likewise, all of them have a bearing on the generation of value for stakeholders in the long term, on the improvement of the relationship between stakeholders and the company, and on management's control and planning mechanisms that protect stakeholders' interests and expectations (Cupertino et al 2019;Jamali 2008;Pirnea et al 2011).…”
Section: The Development Of Csr In the Business Worldmentioning
confidence: 99%
“…1087). This approach, which is largely accepted by both practitioners and academics (i.e., Bohlmann et al, 2018;Chowdhury, Choi, Ennis, & Chung, 2018;Martínez-Conesa et al, 2017;Sarkar & Searcy, 2016;Vanelslander, 2016) "gives equal weight to economic, environmental, and social dimensions" (Hussain, Rigoni, & Orij, 2018;p. 411).…”
Section: Factors Affecting the Csr-innovation Relationshipmentioning
confidence: 99%
“…It "refers to society's expectations that the firm will be profitable in the long term and obtain utilities as incentives and rewards for its efficiency and effectiveness by producing and selling quality goods and services First, when firms are looking to increase their efficiency, they tend to improve their process through cost-cutting practices. These practices lead firms to develop new or improved processes (Bocquet et al, 2013;Chowdhury et al, 2018). Second, all of the internal changes required to improve efficiency can foster the development of unique organizational capabilities (organizational innovations; FIGURE 1 Conceptual model I: CSRinnovation link Bocquet et al, 2013).…”
Section: Factors Affecting the Csr-innovation Relationshipmentioning
confidence: 99%
See 1 more Smart Citation